(untitled) (Research, Society and Development, 2022)
The global organic food market has been growing considerably year by year. In Brazil, the production of organic food, free of agrochemicals, grows at a rate of 20% per year. Thus, understanding how consumers perceive the Attributes, Consequences (benefits) and Values (A-C-V) in relation to these foods is crucial for a better positioning of enterprises in terms of the market they operate. Thus, the present work aims to study the behavior of consumers of organic foods based on the relationships between the Attributes-Consequences-Values (A-C-V) and the Stages of the Purchase Process (EPP). For this, an in-depth analysis of the content of testimonials from consumers of organic food and of scientific works was carried out to identify some of the main aspects that reflect the A-C-V of the organic food consumer. Finally, a framework was proposed that aims to illustrate and contextualize the main thematic elements of this research (A-C-V) and their relationship with the Stages of the Purchasing Process (SPP). As for the methodology, it is a qualitative research with an exploratory and descriptive nature. The research results made it possible to verify that the A-C-V triad, in a way, influences the consumer of organic foods, more specifically regarding their intention to buy, the realization of the purchase and the willingness to make future purchases. It was also possible to synthesize several aspects inherent to organic food and organize them in a framework. The framework made it possible to verify interactions between the variables, making it clearer the different ways that A-C-V can affect the SPP of organic food consumers.